Highly Efficient Multivalent 2D Nanosystems for Inhibition of Orthopoxvirus Particles. Issue 22 (1st September 2016) - Ziem, Benjamin; Thien, Hendrik; Achazi, Katharina; Yue, Constanze; Stern, Daniel; Silberreis, Kim; Gholami, Mohammad Fardin; Beckert, Fabian; Gröger, Dominic; Mülhaupt, Rolf; Rabe, Jürgen P.; Nitsche, Andreas; et al.
Abstract : Efficient inhibition of cell–pathogen interaction to prevent subsequent infection is an urgent but yet unsolved problem. In this study, the synthesis and functionalization of novel multivalent 2D carbon nanosystems as well as their antiviral efficacy in vitro are shown. For this reason, a new multivalent 2D flexible carbon architecture is developed in this study, functionalized with sulfated dendritic polyglycerol, to enable virus interaction. A simple "graft from" approach enhances the solubility of thermally reduced graphene oxide and provides a suitable 2D surface for multivalent ligand presentation. Polysulfation is used to mimic the heparan sulfate‐containing surface of cells and to compete with this natural binding site of viruses. In correlation with the degree of sulfation and the grafted polymer density, the interaction efficiency of these systems can be varied. In here, orthopoxvirus strains are used as model viruses as they use heparan sulfate for cell entry as other viruses, e.g., herpes simplex virus, dengue virus, or cytomegalovirus. The characterization results of the newly designed graphene derivatives demonstrate excellent binding as well as efficient inhibition of orthopoxvirus infection. Overall, these new multivalent 2D polymer nanosystems are promising candidates to develop potent inhibitors for viruses, which possess a heparan sulfate‐dependent cell entry mechanism. Abstract : Efficient inhibition of orthopoxvirus infection by newly designed multivalent 2D nanosystems functionalized with dendritic polyglycerol polymers in a simple "graft from" approach is described in this study. A tunable polysulfation is used to enable virus interaction, which correlates with the degree of sulfation and the grafted polymer density. In conclusion, the innovative 2D architectures have the potential to develop new virus inhibitors.